Penguatan Manajemen Wakaf melalui Pengembangan SDM Profesional dan Literasi Masyarakat di Era Digital - Faujiah, Ani (Journal of Islamic Economics Studies and Practices, 2025)
Contemporary waqf management faces multidimensional challenges characterized by low nazhir professionalism, limited public literacy, and fragmented governance structures that hinder the optimal utilization of waqf assets. Although previous studies emphasize the urgency of strengthening institutional capacity and public education, they often examine these aspects in isolation, creating a research gap in the form of an absence of an integrated model that connects human resource development, community literacy, digital transformation, and governance quality. Drawing on the theories of human resource management, financial literacy, sharia governance, and digital transformation, this study analyzes the interrelation of these four elements in strengthening the modern waqf management ecosystem. The study employs a qualitative literature review of publications from 2018 to 2024, encompassing bibliometric analysis, case studies, quantitative surveys, and qualitative interviews. The findings reveal that competency-based training, nazhir certification, and digital evaluation systems enhance asset management efficiency. Hybrid literacy programs expand public participation, while the integration of technologies such as blockchain, artificial intelligence, and the Waqf Core Performance and Integrity Index (WCPII) reinforces transparency and accountability. The study concludes that strong governance acts as a key moderator determining the effectiveness of synergies among human resources, literacy, and digitalization in achieving sustainable waqf management.